Biological Treatment of Fish Processing Saline Wastewater for Reuse as Liquid Fertilizer - Ching, Yun Chen; Redzwan, Ghufran (MDPI, 2017)
The fish processing sector contributes serious organic pollution loads and high salinity to receiving waters. This research aimed to study the effect of salt (NaCl) concentration on the treatment efficiency of fish processing wastewater in a continuous flow system by natural biodegradation. This research also focused on the use of a laboratory-scale bioreactor, which is operated in an aerobic continuous flow system with a 5-day cycle treatment of three different concentrations of diluted fish processing wastewater (30-, 50-, and 100-fold) with salt concentrations varying from 0% to 7% w/v NaCl. The evaluation of system performance at nine different operating hydraulic retention times (HRT) that range from 2-10 days indicated that the substrate removal rates increase with the increase in HRT along with the increasing wastewater concentration. The optimum biomass yield was found at the 8-day HRT, and the highest substrate removal was obtained at 10-day HRT. The study on 11 different salt contents in wastewater at the optimal HRTs of 10, nine, and eight days showed the existence of inhibition effects on biomass growth and substrate removal from 3.0% salt concentration. The treated wastewater without offensive odor is feasible for its reutilization as an environmental friendly liquid fertilizer.